Peran kesiapan digital, work-life balance, dan stres kerja dalam kepuasan kerja karyawan era digital - Palapa, Gabriel Christian Ivanlie Nistelrooy; Saragih, Susanti (Journal of Management and Digital Business, 2026)
Digital readiness and work-life balance are key factors in shaping employee job satisfaction amid the increasing digitalization of work. Although many studies have examined work-life balance, this study fills a gap by integrating digital readiness as a contextual variable in the digital era. This study aims to analyze the effects of digital readiness and work-life balance on employee job satisfaction and to examine the mediating role of work stress. This study employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected online via a survey of 105 employees in Bandung City who use digital technology in their work. The results indicate that digital readiness has a significant effect on employee job satisfaction. Similarly, work-life balance significantly affects employee job satisfaction. Meanwhile, work stress did not mediate these relationships. These findings suggest that organizational support, in the form of work-life balance policies and adequate digital facilities, can directly enhance employee job satisfaction without necessarily reducing work stress. Theoretically, these findings reinforce Social Exchange Theory in a digital context. In practice, this study recommends HR policies that leverage digital facilities and promote work-life balance for organizations.